Fiscal Decentralization Impact on Regional Development - Gariba, Mohammed Ibrahim; Provazníková, Romana (International Hellenic University, 2021)
This paper aims to examine how fiscal decentralization may influence regional development in selected CEE countries (the Czech Republic, Slovakia, and Poland). Previous research on this question has primarily focused on just the relationship between fiscal decentralization and growth. This paper further examines the effect of subnational revenue, subnational expenditure, and transfers to subnational governments on regional development, i.e., GDP growth rate and Human development index (HDI). Data from Organization for Economic Cooperation and Development (OECD) from 2010 to 2019 at the subnational government finance for the examined countries were used. The analysis involved analyzing the three models by focusing on each individual model of the CEE countries to assert the results' strength and veracity. We find that decentralized revenues positively influence GDP growth rate and HDI in selected CEE countries with overall positive significant results in all countries. There is no significant effect for subnational expenditure in the two countries, the Czech Republic and Poland, except Slovakia. Although this impact is much less clear in some countries, transfers, however, showed no positive significance at all in each of the selected countries. Because the dependent and independent data are linear variables, we adopted the ordinary least squares regression analysis method.
Vliv fiskální decentralizace na regionální rozvoj.
Keywords: fiscal decentralization; regional development; OLS regression.; fiskální decentralizace; regionální rozvoj; OLS regrese